Understanding of Genetic Information and RNAi Therapeutic Application in Medical Faculty Students in Northeast Sri Lanka and the Implications for Genetics Education - Marikar, Faiz M.M.T.; Kulugammana, Manel B.C.N.; Karawita, Karawitage R.L.; Jayathilaka, Aravinda S.; Hettiarachchi, Dau.; Kalainesan, Kesaven; Kumara, Eranda I.; Kumara, Kodithuwakkulage M.P. (Journal of Research in Educational Sciences; Vol 5 No 1 (2014): JRES, Volume V, Issue 1(7), 2014DO - 10.14505/jres.v5.7.02, 2014)
This study examines students’ understanding of the normative connections between key concepts of genetics, and RNAi and underlying biological principles that are critical for an in-depth understanding of RNAi therapeutic application on Medical field. Using a structural questionnaire, we examine randomly selected Medical faculty students’ understanding of genetic relationships at Faculty of Medicine and Allied Sciences, University of Rajarata, Sri Lanka. A total of 80 Medical faculty students participated in this study and completed written questionnaire on genetics and RNAi therapeutic application. Findings from this study were there is a strong positive response on basic genetics studies in this content, but when it considers knowledge on RNAi and new technology based on RNAi therapeutic application is poorly understood. Almost all the students had a good knowledge on DNA but not the relationship between gene and DNA. Specifically, students were requested to demonstrate an integrated understanding of the RNAi therapeutic application, almost 96% of them unable to give an example for it, and also some students struggled to explain it. Outcome of this study is preliminary in nature; the results provide cause for concern over the status of genetics education in Sri Lanka need to uplift.